Assessing the quality of health services applied research 5qs in Baghdad teaching hospital - عبد الوهاب, نادية لطفي; كاظم, حيدر منصور (Journal of Economics and Administrative Sciences, 2016)
Abstract       This research aims to assess and measure the quality of health services provided by the Baghdad Educational Hospital using  five dimensions of 5Qs , Developer model by (Zinelidin), 2006), the problem of the research is to try to determine the quality of health services provided at the hospital as well as the investigation of the existence of the elements of quality contribute to achieve the requirements of customers and their needs, and used for the purposes of this research two approaches, first used Applied Research to 5Qs dimension model and use the Checklist as a Key tool to collection and analysis of data and the second descriptive analytical method to get feedback from customers (patients) for health services provided to them by opinion surveys to their views about these services , as well as the data and information obtained from the records and documents of the hospital its various sections, and research found a set of conclusions which, the applicability of the dimensions 5Qs model in the hospital and on the quality of health services, showed measuring these dimensions good results The order of dimensions in the order of importance (quality of the process, the quality of the interaction, quality goals, the infrastructure "core" quality, quality of public feeling) The total quality (70%), which means the possibility of adopting this form to assess the quality of hospital services, has recommended the search of the need adoption of the dimensions 5Qs model to evaluate the quality of services provided to patients within the Baghdad Educational Hospital as these dimensions is a kind of modern indicators that provide a comprehensive assessment of the quality of health service in the hospital.